(untitled) (Journal of Contemporary Educational Policies and Practices, 2024)
Statistical reasoning (SR) is an essential skill for students in studying statistics. This study aims to develop SR for university students through an appropriately designed course in statistics. Employing a quasi-experimental design, this study evaluated students’ SR changes as they participated in a research-informed statistics course, designed to integrate statistical reasoning. The results showed that the course helps students improve their SR, with their scores increased by 23% from the pre-test to the post-test. Specifically, the SR scores on measures of central tendency of the experimental class increased by 8%; while the SR scores on the measures of variability of the experimental class increased by 34%. Suggestions about curriculum and teaching are included, such as offering opportunities for statistical investigations with real data; going deeper into building and understanding formulas; and training lecturers to teach statistics using approaches that are different from traditional teaching methods, as well as evaluating students’ statistical learning with reliable tools.